Bisphosphonate use and incident cardiovascular events among older breast cancer survivors. (October 2019) - Gegechkori, Nana; Egorova, Natalia; Mhango, Grace; Wisnivesky, Juan P.; Lin, Jenny J.
Abstract: Background: Cardiovascular disease (CVD) is a leading cause of mortality in early-stage breast cancer survivors. Recent studies suggest that bisphosphonates may decrease CVD risk in older patients. Objective: This study sought to assess whether bisphosphonate use is associated with lower rates of incident CVD events among early-stage breast cancer survivors. Methods: Longitudinal, population-based cohort study was conducted by using data from the Surveillance, Epidemiology and End Results registry linked to Medicare claims. We identified women >65 years with no history of CVD who were diagnosed with stage 0-III primary breast cancer between 2007 and 2010. Our primary outcome was a composite of incident angina pectoris, myocardial infarction, atrial fibrillation/flutter, heart failure, or stroke within 36 months of cancer diagnosis. Bisphosphonate use was defined as the presence of ≥1 pharmacy claim from 6 months prior to cancer diagnosis to the incident CVD event. We used propensity scores to create a matched group of breast cancer survivors without bisphosphonate exposure to compare rates of incident CVD events. Results: A total of 2178 breast cancer survivors had ≥1 bisphosphonate prescription; the average length of bisphosphonate use was 15 months. Analyses of the matched data showed that 13.0% of bisphosphonate users and 23.4% of non-bisphosphonate users experienced an incident CVD event (p < 0.0001) after breast cancer diagnosis. Bisphosphonate use was significantly associated with fewer incident CVD events (hazard ratio: 0.51, 95% confidence interval: 0.44 to 0.59). Conclusions: Bisphosphonate use is associated with lower incidence of CVD events among older early-stage breast cancer survivors. Future studies should prospectively evaluate whether bisphosphonate use can decrease CVD incidence. Highlights: Cardiovascular disease (CVD) is a leading cause of mortality in early-stage breast cancer survivors. Recent studies suggest that bisphosphonates may decrease CVD risk in older patients. Bisphosphonate use was significantly associated with fewer incident CVD events (HR: 0.51, 95%, CI: 0.44 to 0.59). Abstract : Condensed Abstract: Cardiovascular disease (CVD) is one of the main causes of death in women with early-stage breast cancer. Recent observational studies suggest that bisphosphonate use may be associated with lower incidence of CVD in older patients. Our study provides further evidence that bisphosphonate use is associated with reduced incident CVD events in older early-stage breast cancer survivors. Given that CVD is the primary cause of death among older breast cancer survivors with early-stage cancer, reduction in CVD incidence may have a substantial impact on overall morbidity and mortality in this group of patients.